OC-013 Knife Assisted Resection (kar) Of Large And Refractory Colonic Polyps At A Western Centre: Feasibility, Safety And Efficacy Study To Guide Future Practice. (9th June 2014) - Bhattacharyya, R; Longcroft-Wheaton, G; Bhandari, P
Abstract : Introduction: ESD enables large lesions to be resected en bloc. This reduces recurrence, but ESD is technically challenging with high complication rates and hence not widely practiced in the west. We have used a novel Knife Assisted Resection (KAR) technique. We aim to evaluate the outcome of KAR in the treatment of large and refractory colonic polyps and identify polyp features that can predict complications and recurrence after KAR. Methods: Cohort study of patients referred to our centre for resection of refractory polyps. All patients who had KAR of colonic polyps >20 mm in size from 2006 to Feb 2013 were included. All procedures were performed by a single experienced endoscopist. The technique starts with submucosal (SM) injection followed by mucosal incision using a dual knife (Olympus KD-650L). This is followed by variable degrees of SM dissection and completion of circumferential mucosal incision. Finally a snare assisted resection is performed either en bloc or piecemeal, depending on the polyp size and extent of SM dissection. Results: 127 polyps in 127 patients of mean age 71 years. Mean polyp size 46 mm (20–170 mm). 27% were >50 mm. 27% were scarred from past attempted resection. 26% were in the right colon. En bloc resection: 58/127(46%). Size <50 mm was a significant (p = 0.001) predictor of en bloc resection (88 vs. 12%). The complication rate was 11/127(8.6%) with 5(3.9%) bleeds, 4(3.1%) diathermy damage to muscle fibres and 1(0.78%) perforation. Complications were not linked to polyp size, scarring or resection site. A single patient with perforation required surgery. All other complications were managed endoscopically. The recurrence rate was 14/106(13%). This was significantly higher for polyps >50mm (p = 0.009) and in scarred polyps (p = 0.024) . On sub-analysis of unscarred polyps, polyps ≤50 mm with no scarring had a very low recurrence rate of 3.2% as compared to 25% in polyps >50 mm (p = 0.005) . Factors associated with recurrence Conclusion: This is the largest reported western series demonstrating the feasibility, safety and efficacy of KAR for large and refractory polyps, with or without scarring, at all colonic sites. Our data demonstrates that complications of KAR are not related to size but the recurrence rate is. Size >50 mm and scarring seem to be predictors of recurrence. We propose flat polyps 20–50 mm in size as the ideal indication for KAR in the western setting. Disclosure of Interest: None Declared.